Effects of survey response mode, purported topic, and incentives on response rates in human dimensions of fisheries and wildlife research. Issue 3 (4th May 2022) - Anderson, Leif; Jans, Matt; Lee, Adam; Doyle, Christopher; Driscoll, Heather; Hilger, James
ABSTRACT: Incorporating human values and behavior into natural resource management has been linked to more sustainable and efficient outcomes. Estimating these values often requires survey-based data collection. Declining response rates have amplified the need to more fully understand the influence of survey design features on response. In this study, we used an experiment to measure the effect of response mode (mail vs. web), purported topic (recreation vs. saltwater angling), and incentives ($0, $2, $5) on two outcomes of interest: screener response and extended questionnaire response. The context is a survey of saltwater anglers on the Pacific coast of the United States. We found increased probabilities of screener response with an incentive, with a stronger effect within the mail response mode. At the extended questionnaire stage, we found some effect of survey response mode that was moderated by topic and incentive. Our results help inform future survey efforts.